If the 7th and 13th term of an arithmetic progression are 34 and 64 respectively yhen the common difference is
Answers
Answered by
0
Answered by
2
Hey there !!
➡ Given :-
→ 7th term of AP (
) = 34.
→ 13th term of AP (
) = 64.
➡ To Find :-
→ The common difference (d).
➡ Solution :-
→
= 34.
=> a + ( n - 1 )d = 34.
=> a + ( 7 - 1 )d = 34.
=> a + 6d = 34........ (1).
And,
→
= 64.
=> a + ( n - 1 )d = 64.
=> a + ( 13 - 1 )d = 64.
=> a + 12d = 64........... (2).
▶ Substracte in equation (1) and (2), we get
a + 6d = 34.
a + 12d = 64.
(-)..(-)........(-).
__________
=> - 6d = - 30.
=> d =![\frac{ - 30 }{ - 6 } . \frac{ - 30 }{ - 6 } .](https://tex.z-dn.net/?f=+%5Cfrac%7B+-+30+%7D%7B+-+6+%7D+.+)
![\huge \boxed{ \boxed{ \bf \therefore d = 5. }} \huge \boxed{ \boxed{ \bf \therefore d = 5. }}](https://tex.z-dn.net/?f=+%5Chuge+%5Cboxed%7B+%5Cboxed%7B+%5Cbf+%5Ctherefore+d+%3D+5.+%7D%7D+)
✔✔ Hence, it is proved ✅✅.
____________________________________
THANKS
#BeBrainly.
➡ Given :-
→ 7th term of AP (
→ 13th term of AP (
➡ To Find :-
→ The common difference (d).
➡ Solution :-
→
=> a + ( n - 1 )d = 34.
=> a + ( 7 - 1 )d = 34.
=> a + 6d = 34........ (1).
And,
→
=> a + ( n - 1 )d = 64.
=> a + ( 13 - 1 )d = 64.
=> a + 12d = 64........... (2).
▶ Substracte in equation (1) and (2), we get
a + 6d = 34.
a + 12d = 64.
(-)..(-)........(-).
__________
=> - 6d = - 30.
=> d =
✔✔ Hence, it is proved ✅✅.
____________________________________
THANKS
#BeBrainly.
Similar questions